2015
DOI: 10.1007/s10669-015-9538-5
|View full text |Cite
|
Sign up to set email alerts
|

Inventory of ethnobotanicals and other systematic procedures for regional conservation of medicinal and sacred plants

Abstract: The plant diversity of western Madhya Pradesh is reducing at the fast rate due to anthropogenic disturbances and environmental degradation. Disturbance is a major factor responsible for the fragmentation of forest vegetation; as a result, there is a preponderance of small patches, and some of them are still preserved as sacred groves because of strong religious beliefs held by the indigenous people of Jhabua district of western Madhya Pradesh. Dungari mata sacred grove is situated near Katthiwada village in Jh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The dominance of these native and wild plants in home gardens was by Whitney et al (2018a,b) and Kala (2010). Our study found a variety of threatened species, including Abrus precatorious and A. paeoniifolius as endangered, B. lanzan and S. febrifuga as vulnerable, and Woodfordia fruticosa and Aegle marmelos are near threatened, which is consistent with the findings of Wagh and Jain (2015) in central India.…”
Section: Conservation Of Native Plant Speciessupporting
confidence: 91%
“…The dominance of these native and wild plants in home gardens was by Whitney et al (2018a,b) and Kala (2010). Our study found a variety of threatened species, including Abrus precatorious and A. paeoniifolius as endangered, B. lanzan and S. febrifuga as vulnerable, and Woodfordia fruticosa and Aegle marmelos are near threatened, which is consistent with the findings of Wagh and Jain (2015) in central India.…”
Section: Conservation Of Native Plant Speciessupporting
confidence: 91%
“…Sacred sites/shrines have large harbor of medicinally important plant species 10,11 . The herbal medicine provided the therapeutic requirement for>80% people of the world, which mostly cover the remote areas of developing countries 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the conservation practices, the unique assemblage of the sacred and medicinal plant is found. Most of the study on medicinal plant of sacred sites in India is reported from Himalayan and south India region 19,9 while, few study were reported from central and eastern India 20,11 .…”
Section: Introductionmentioning
confidence: 99%